Is early partnership formation instrumental for fertility in Germany? Influences of fertility orientations on partnership transitions - Okka Zimmermann (Comparative Population Studies (CPoS), 2021)
Using panel data from childless respondents of the German Family Panel (pairfam, n=3,802 respondents), this paper investigates whether fertility orientations (biographical orientations with respect to fertility) influence the risk of different partnership transitions among German men and women over the age of 18 (for n=14,572 observation periods between two panel waves). Significant influences are found for both gender and partnership transition types, and are generally stronger among men than women and for the transition to a coresidential as opposed to a romantic partnership. Uncertainty about anticipated fertility has a stronger negative impact on transition risks among men than among women. Results strongly suggest that the early stages of the partnership formation process are instrumental in terms of future fertility in Germany, at least to some degree. This indicates that a more comprehensive conceptualisation and analysis of fertility within the life course paradigm (as suggested by Huinink/Kohli 2014) should consider the impacts of fertility orientations on life course events in other dimensions, especially among men. Viewed more broadly, the results also underline two factors: the role of agency in coordinating life course dimensions in time and space in order to maximise individual welfare; and the importance of considering the impacts that anticipation of future life course events will have, as suggested by different theoretical approaches.
urn:nbn:de:bib-cpos-2021-01en7
Keywords: 300; Fertility; Partnership; Coresidential partnership; Life course; Biographical orientations